Vitamin D Supplementation for Prevention of Type 2 Diabetes Mellitus: To D or Not to D? - Pittas, Anastassios G (J Clin Endocrinol Metab, 2020)
CONTEXT: Over the last decade, vitamin D has emerged as a risk determinant for type 2 diabetes and vitamin D supplementation has been hypothesized as a potential intervention to lower diabetes risk. Recently, several trials have reported on the effect of vitamin D supplementation on diabetes prevention in people with prediabetes. EVIDENCE ACQUISITION: A comprehensive literature review was performed using PubMed, Embase, and ClinicalTrials.gov to identify: (1) recent meta-analyses of longitudinal observational studies that report on the association between blood 25-hydroxyvitamin D (25[OH]D) level and incident diabetes, and (2) clinical trials of adults with prediabetes that have reported on the effect of vitamin D supplementation on incident diabetes. EVIDENCE SYNTHESIS: Longitudinal observational studies report highly consistent associations between higher blood 25(OH)D levels and a lower risk of incident diabetes in diverse populations, including populations with prediabetes. Trials in persons with prediabetes show risk reduction in incident diabetes with vitamin D supplementation. In the 3 large trials that were specifically designed and conducted for the prevention of diabetes, vitamin D supplementation, when compared with placebo, reduced the risk of developing diabetes by 10% to 13% in persons with prediabetes not selected for vitamin D deficiency. CONCLUSIONS: Results from recent trials are congruent with a large body of evidence from observational studies indicating that vitamin D has a role in modulating diabetes risk. Participant-level meta-analysis of the 3 largest trials should provide a more refined estimate of risk reduction and identify patient populations that are likely to benefit the most from vitamin D supplementation.